Pembuatan dan Karakteristik Serbuk Piezoelektrik Pb(Zr,Ti)03 tanpa subtitusi dan dengan Nb substitusi - Silvester Tursiloadi (Jurnal Kimia Terapan Indonesia, 1998)
The characteristics of chemically prepared piezoelectric PZT and doped PZT with niobium (PNZT) were investigated. PZT 55/45, both unmodified and doped with Nb2O5 were prepared by the hydrolysis of metal alkoxides and solid state reaction from PbO, ZrO, and TiO,. The average particle size was 0.45 um. X-ray diffraction results indicated that transformation of the amorphous precipitate be came well crystallized PZT after heating at 500 °C for 6 hours. DTA results suggested theformation of an intermediate PbTiO3 phase at 490 °C. Using X-ray diffractton can be investigated occurring of both tetragonal and rombohedral ferroelectric PZT phases. That case depends on the initial mixing of chemical composition. The PZT powders which prepared from alkoxides were agglomerated easly at low temperature calcining. Poor sintered bodies will he resulted it was calcinated above 600°C. Powders calcined at 500 °C for 6 hours and sintered at 1200 °C produced high body densities approaching 95% of theoretical density.The experimental results suggest that intimate mixing of constit uents during the hdrolyt ic decomposition produces a homogeneous powder. However, differences in the rate hydrolysis or polymerization of the respective metal alkoxides fend to couse the stoichiometric results difficult to be found.